PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN DI UNIVERSITAS UDAYANA DENGAN INFORMASI ASIMETRI DAN MOTIVASI SEBAGAI PEMODERASI - Priliandani, Ni Made Intan; Astika, I. B. Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This research was conducted at the Udayana University. This study took university as the object because education is an important factor in establishing the human characteristic and mind. The purpose of this study was to test the effect of budgetary participation on budgetary slack with asymmetric information and motivation as moderating variables. The population of this study was 123 people taken from Udayana University, which consists of the Deans, the first Vice of Dean, the second Vice of Dean, the third Vice of Dean, the Director of Postgraduate Program, the first Assistant Director, the second Assistant Director, Head Section and Sub-section of each faculty. The sampling technique used in this study was saturated sampling technique in which all members of the population became the sample. The data analysis technique used in this study was a simple linear regression analysis and Moderated Regression Analysis (MRA). The result of this study shows that budgeting participation influences the budgetary slack. Another result shows that the interaction within variables of asymmetric information may moderate relationship between budgetary participation and budgetary slack. Other moderating variables such as motivation cannot moderate the relationship between budgetary participation with budgetary slack.
Keywords: budgetary participation, asymmetric information, motivation, budgetary slack